The Effect Of Intellectual Capital And Islamic Performance Index On Financial Performance - Yusro Rahma (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
This research aims to examine intellectual capital and islamic performance index (IPI) on financial performance with profitability approach. Intellectual capital proxied by Value added intellectual capital (VAIC) (VACA, VAHU and STVA) adopted by Pulic (1998). IPI proxied by Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), Islamic Income Ratio (IIR), Profitability by Return on Assets (ROA). This research used 10 samples of islamic bank listed on Indonesia Financial Services Authority (OJK) in period 2012 to 2015. Multiple regression used to examine the hypothetical research. Results of this research provide evidence that value added intellectual capital (VAIC) positively and significantly influence toward return on asset. Profit Sharing Ratio (PSR) negatively and significantly no influence toward return on asset. Zakat Performance Ratio (ZPR) positively and significantly influence toward return on asset. Islamic Income Ratio (IIR) positively and significantly no influence toward return on asset with significance alpha 5%, but with significance alpha 10% Islamic Income Ratio (IIR) positively and significantly influence toward return on asset